2019
DOI: 10.1007/s10620-019-05492-y
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Experience with Tofacitinib in IBD at a Tertiary Center

Abstract: Background and aims: Many inflammatory bowel disease (IBD) patients do not respond to medical therapy. Tofacitinib is a first in class, partially selective inhibitor of Janus kinase, recently approved for treating patients with ulcerative colitis (UC). We describe our experience with the use of tofacitinib for treatment of patients with moderate-to-severe IBD. Methods: This is a retrospective, observational study of the use of tofacitinib in IBD. Patients with medically resistant IBD were treated orally with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
74
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 17 publications
11
74
2
Order By: Relevance
“…Several factors may contribute to this observation, including the relative shorter duration of follow‐up, the intention‐to‐treat design as well as corticosteroid taper for a subgroup of patients during follow‐up. Indeed, other real‐life cohort confirmed this finding (week 8 clinical remission 33%, week 26:25%) . To date, only two real‐world retrospective cohorts have reported the effectiveness and safety of patients receiving tofacitinib before market authorisation.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Several factors may contribute to this observation, including the relative shorter duration of follow‐up, the intention‐to‐treat design as well as corticosteroid taper for a subgroup of patients during follow‐up. Indeed, other real‐life cohort confirmed this finding (week 8 clinical remission 33%, week 26:25%) . To date, only two real‐world retrospective cohorts have reported the effectiveness and safety of patients receiving tofacitinib before market authorisation.…”
Section: Discussionmentioning
confidence: 67%
“…A single‐centre cohort study reported 58 patients (93% anti‐TNF and 81% vedolizumab exposed) treated with tofacitinib. After 26 weeks of treatment, 21% was in corticosteroid‐free clinical remission (physician global assessment) . In a compassionate early‐access programme in France, 38 patients received tofacitinib after failure of both anti‐TNF and vedolizumab treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Moreover, tofacitinib has an increased risk for certain viral infections (eg, herpes zoster infection). [59][60][61] Thus, treatment indication needs to be discussed in individual cases. At this point, no evidence for stopping these treatments in patients with remission exists.…”
Section: Immunotherapy In Ibd: Potential Effects On Covid-19mentioning
confidence: 99%
“…Of 4789 patients treated with tofacitinib in phase II, III and LTE studies, 259 patients had serious infections (3.09 events per 100 PY [95% CI 2.73, 3.49]), and the most common infection was pneumonia 92 . Higher doses of 10 mg twice daily as opposed to 5 mg twice daily, age >65 years, corticosteroids >7.5 mg/d and diabetes were also independent factors associated with increased serious infection risk 92,93 . Therefore, patients on tofacitinib should be maintained on the lower 5 mg twice daily dose compared to 10 mg twice daily where possible and weaned off corticosteroids.…”
Section: Management Of Immunosuppression With Covid‐19mentioning
confidence: 99%